Evaluasi Pengelolaan Organisasi Non Profit Untuk Menunjang Transparansi Dan Akuntabilitas Bagi Donatur - Agung Sri Wardani; Bambang Herwanto; Ratnawati Hari Prayitno (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2018)
Financial statement is one of the essential thing in managing finance in an organization. Both profit oriented organizations and non profit oriented organizations requires relevant, reliable, comparable and understandable information in financial statements presented. Moreover, the non profit organizations, which the largest source of funding is donated from donors, the possibility of fraud becomes bigger. It is usually done by several parties, even by the management itself. Therefore, the diclosure of relevant, reliable, comparable, and understandable financial statements, are necessary done by the non profit organizations. The disclosure of financial statement needs a healthy organization management, good strategic management, finance report based on the accounting standards (PSAK 45) and good technology utilization. The technology utilization by web based financial statement are expected to be faster in presenting the non profit organization financial statement. With the stages of process that are undertaken, hopefully it will increase transparency of accountability for the donors.